ChemInform Abstract: Chemoselective Boronic Ester Synthesis by Controlled Speciation. Issue 15 (April 2015) - Fyfe, James W. B.; Seath, Ciaran P.; Watson, Allan J. B.
Abstract: The solution speciation of boronic acids can be chemoselectively controlled to enable the formal homologation of boronic acid pinacol esters.